Whole-Genome Analysis Illustrates Global Clonal Population Structure of the Ubiquitous Dermatophyte Pathogen Trichophyton rubrum. Issue 4 (1st April 2018) - Persinoti, Gabriela F; Martinez, Diego A; Li, Wenjun; Döğen, Aylin; Billmyre, R Blake; Averette, Anna; Goldberg, Jonathan M; Shea, Terrance; Young, Sarah; Zeng, Qiandong; Oliver, Brian G; Barton, Richard; et al.
Abstract: Dermatophytes include fungal species that infect humans, as well as those that also infect other animals or only grow in the environment. The dermatophyte species Trichophyton rubrum is a frequent cause of skin infection in immunocompetent individuals. While members of the T. rubrum species complex have been further categorized based on various morphologies, their population structure and ability to undergo sexual reproduction are not well understood. In this study, we analyze a large set of T. rubrum and T. interdigitale isolates to examine mating types, evidence of mating, and genetic variation. We find that nearly all isolates of T. rubrum are of a single mating type, and that incubation with T. rubrum "morphotype" megninii isolates of the other mating type failed to induce sexual development. While the region around the mating type locus is characterized by a higher frequency of SNPs compared to other genomic regions, we find that the population is remarkably clonal, with highly conserved gene content, low levels of variation, and little evidence of recombination. These results support a model of recent transition to asexual growth when this species specialized to growth on human hosts.